Clientelism, Partyarchy and Democratic Backsliding: A Case Study of Local Government Elections in Bangladesh. (March 2019) - Sarker, Abu Elias; Nawaz, Faraha
In a developing country like Bangladesh, the devolved local government system is widely recognized as one of the key institutional forms for the citizen-centric public service delivery system and ensuring democratic governance at the grassroots level. However, the democratic nature of local governments and their effective role in rendering services are contingent upon the political and institutional environments of the country. Competitive electoral process is key to local democratic governance. The purpose of this article is to analyze the implications of contemporary political order and institutional environments for the proper functioning of the Union Parishad (council), the lowest tier of the local government system in Bangladesh. More specifically, this study will reflect on how political clientelism, partyarchy and institutional environments have stymied competitive electoral politics at the local level which may result in democratic backsliding.